Some Results on Topical Functions and Upward Sets (Analysis in Theory and Applications, 2011)
The purpose of this paper is to introduce and discuss the concept of topical functions on upward sets. We give characterizations of topical functions in terms of upward sets.
Keywords: topical function; upward set; ordered Banach space.